Collecting resource use data for economic evaluation in a prison setting with a focus on self-harm: the Prison Data Inventory (Self-Harm) (PDI (SH)) - Robinson, Louise; Gutridge, Kerry; Meacock, Rachel; Barrett, Barbara; Abel, Kathryn M. (Frontiers in Psychiatry, 2025)
IntroductionSelf-harm is a common and escalating problem in prisons, particularly in women. Understanding and measuring the costs of self-harm allow high-quality evaluation of new interventions. Here, we describe the co-development of a new resource inventory, the Prison Data Inventory (Self-harm).MethodsAn existing forensic resource use tool, the SF-SUS, was adapted with prison staff and people with experience of being in prison.ResultsPiloting showed that the tool takes researchers approximately two hours to complete per person.DiscussionThis tool will allow use of existing prison data to improve the evidence base for reducing self-harm in prisons. In turn this will enable policy makers and commissioners to allocate resources most effectively, improving clinical outcomes.